TAX INNOVATION, DIGITAL PAYMENT SYSTEMS, AND FINANCIAL SUSTAINABILITY OF MSMES: TAX COMPLIANCE AS MEDIATING - Heliani, Heliani; Rusdiansyah, Nurul (JRAK, 2026)
Formally registered MSMEs in Indonesia face growing fiscal and technological pressures that may affect their financial performance and long-term sustainability. This study aims to examine how tax innovation and payment system digitalization influence financial performance and financial sustainability through tax compliance. Using an explanatory quantitative design, data were collected from 455 formal MSMEs through a structured questionnaire and analyzed using SEM-PLS. The findings show that tax compliance significantly improves financial performance and financial sustainability and partially mediates the effects of tax innovation and digital payment systems. In addition, tax innovation and digital payment adoption directly strengthen compliance and contribute positively to financial outcomes. These results indicate that sustainable MSME finance depends not only on operational efficiency but also on institutional adaptation and compliant fiscal behavior. This study contributes to MSME taxation literature by integrating agency and institutional perspectives to explain the role of compliance in strengthening financial sustainability.